Summarizing information : (Springer, 1998)
Summarizing is the process of reducing the large volume of information in something like a novel or a scientific paper to a short summary or abstract comprising only the most essential points. Summarizing is frequent in everyday communication, but it is also a professional skill for journalists and scientific writers. Automated summarizing functions are urgently needed by Internet users who wish to exploit the information available without being overwhelmed. This book presents the state of the art of summarizing and surveys related research; it deals with everyday and professional summarizing as well as computerized approaches. The author focuses in detail on the cognitive processes involved and supports this with a multimedia simulation system on the accompanying CD-ROM (for Mac OS 7.5 and Windows 95).